Peningkatan Kreativitas Seni Rupa Siswa Melalui Pengelolaan Kelas Berbasis Project Based Learning - Ananta Maulida; Utomo Utomo (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2026)
This study aims to describe the improvement of student creativity in art learning through Project-Based Learning (PjBL) classroom management in the fourth grade of Citamiang Public Elementary School, including the classroom management conditions and the implementation of PjBL itself. A descriptive quantitative approach was used with 30 fourth-grade students as subjects, selected through saturated sampling. Instruments included observation sheets, Likert-scale questionnaires, and interview guidelines. Data were analyzed descriptively using percentage calculations and score interval categorization. Results showed that classroom management prior to PjBL was suboptimal, marked by a less conducive environment and theory-heavy learning. PjBL-based classroom management, implemented through six systematic stages, successfully created a conducive learning atmosphere and active student involvement. A significant increase in creativity was found, with 53.33% of students in the very high category and 40% in the high category, with an average score of 64.3. The study concludes that PjBL-based classroom management is effective in increasing student creativity in art learning in the fourth grade at Citamiang Public Elementary School.